Assessing Collaboration: Alternative Measures and Issues for Evaluation. (September 2018) - Greenwald, Howard P.; Zukoski, Ann P.
This essay addresses challenges in evaluating collaboration by examining two distinct approaches to its measurement. Evaluators frequently assess collaboration on the basis of relationships, climate, and expectations (RCE), and, less often, via extent of collaboration (EC). RCE measures are based on perceptions by coalition members regarding satisfaction with the collaboration, representativeness of the surrounding community, confidence in the leadership, and related areas. EC measures reflect more direct and concrete features of coalitions, such as regularity of communication and commitment of resources. An illustrative study of programs sponsored by a private foundation and a federal agency compares these approaches, finding that RCE and EC measures reflect different underlying features of collaboration and that higher levels of collaboration are likely to be found when evaluators use RCE indicators. Substantively, the study finds large differences in extent of collaboration across areas of operation within each program and a rarity of very high levels of collaboration in most areas. Both face validity and findings from the illustrative study suggest that EC is the more essential measure of collaboration. Comparison of these measures raises issues for both evaluation and grant making.